2019
DOI: 10.21608/aadj.2019.60191
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Rich Fibrin Combined with Nano Crystalline Hydroxyappatite in Treatment of Grade II Mandibular Furcation Defect

Abstract: Aim: This study aims to evaluate the effect of Platelet Rich Fibrin combined with Nano crystalline Hydroxy appatite bone graft on grade II mandibular furcation involvement. Subjects and methods: Thirty patients having grade II mandibular furcation defects, with vertical probing depth (VPD) ≥5mm and horizontal clinical attachment level (HCAL) ≥3mm. Following phase I therapy were classified into two groups, group1 received NcHA bone graft and group 2 received NcHA+PRF. Clinical and radiographic parameters were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Mohamad Fouad Edrees et al completed a study to evaluate the effect of platelet rich fibrin combined with nano-hydroxyapatite bone graft in mandibular grade II furcation as opposed to the bone graft alone. The results showed increased attachment gain in the test group with PRF [ 24 ]. Similar studies were performed by Pradeep et al [ 25 ], Attia AM [ 26 ], Elgendy and Abo [ 27 ] and Siddiqui ZR [ 28 ] where improved regeneration and bone fill was noted when PRF was used along with the bone graft.…”
Section: Discussionmentioning
confidence: 99%
“…Mohamad Fouad Edrees et al completed a study to evaluate the effect of platelet rich fibrin combined with nano-hydroxyapatite bone graft in mandibular grade II furcation as opposed to the bone graft alone. The results showed increased attachment gain in the test group with PRF [ 24 ]. Similar studies were performed by Pradeep et al [ 25 ], Attia AM [ 26 ], Elgendy and Abo [ 27 ] and Siddiqui ZR [ 28 ] where improved regeneration and bone fill was noted when PRF was used along with the bone graft.…”
Section: Discussionmentioning
confidence: 99%
“…Mixture of Nanocrystalline hydroxyapatite (NcHA) and platelet rich fibrin (PRF) was compared with NcHA alone by Attia, 2016 , Edrees et al, 2019 in treatment of class II furcation defects where they found that the PRF in conjunction with the NcHA bone graft demonstrated clinical benefits that were greater than those achieved by the NcHA alone at 12 months’ follow-up. Furthermore, PRF's adjunctive impact has been found to be a promising and effective therapy for class II furcation defects.…”
Section: Discussionmentioning
confidence: 99%
“…Histological examination of the regenerated tissue as well as strategies to enhance growth factor supply when employing PRF could be incorporated in further research. Edrees et al 2019 -NcHA -NcHA + PRF 30/30 Baseline 6 months 12 months Both NcHA and NcHA with PRF improved clinical parameters and bone density considerably. When PRF was used in conjunction with NcHA, the results were clinically and radiographically significant when compared to NcHA bone graft alone.…”
Section: Methodsmentioning
confidence: 99%